Self-repairing factor-containing high-toughness anti-cracking waterproof coating and preparation method thereof
By introducing materials such as acrylate-polyurethane blend emulsion and HDI microcapsules into waterproof coatings, the problems of insufficient toughness and lack of self-healing function of traditional coatings are solved, and a highly tough and self-healing waterproof coating is achieved, which can adapt to deformation of the base layer and reduce maintenance costs.
Patent Information
- Application Number
- CN202511114498.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-11
- Publication Date
- 2025-10-17
- Estimated Expiration
- 2045-08-11
AI Technical Summary
Traditional waterproof coatings lack toughness in special scenarios, are prone to cracking, cannot adapt to the expansion and contraction of the base layer, and lack self-repair capabilities, leading to water penetration and increased maintenance costs.
Using materials such as acrylate-polyurethane blend emulsion, HDI microcapsules and carbon nanotubes, HDI microcapsules are prepared by interfacial polymerization to form self-repairing function and improve the toughness and crack resistance of the coating.
It achieves high toughness, crack resistance and self-repairing function, prolongs the service life of the coating, reduces maintenance costs, adapts to the expansion and contraction of the base layer caused by changes in temperature and humidity, and improves the waterproof effect.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of waterproof coating preparation, and relates to a high-toughness anti-cracking waterproof coating containing a self-repairing factor and a preparation method. BACKGROUND
[0002] Waterproof coating is an indispensable material in building engineering, and its performance is directly related to the waterproof effect and service life of the building. With the development of building technology, the performance requirements of waterproof coating are becoming higher and higher, especially in special scenarios such as floor heating rooms, bridges, underground garages, etc. Traditional waterproof coating often cannot meet the requirements.
[0003] Traditional waterproof coating mainly has the following problems: first, the function is relatively single, mainly focusing on basic waterproof performance; second, the toughness is insufficient, and cracks are easily generated when the temperature changes or the structure deforms; third, the breaking elongation is low, and it cannot adapt to the expansion and deformation of the base; fourth, it does not have a self-repairing function, once a tiny crack appears, water can easily penetrate and cause more extensive damage. For example, in some areas with large temperature changes, the base of the building will expand and deform, causing ordinary waterproof coating to crack, and then allowing water to penetrate, affecting the service life of the building and the safety of the internal structure. These problems not only affect the waterproof effect, but also increase maintenance costs and safety hazards. Because once the waterproof coating is damaged by external forces, such as accidental damage during construction or wear and tear during long-term use, traditional coating cannot self-repair and can only be repaired by manual repair, which not only increases maintenance costs, but also risks exacerbating the problem if repair is not timely.
[0004] In order to solve these problems, researchers have begun to add various functional materials to waterproof coating. In addition, how to ensure the uniform dispersion and stability of these materials in the coating, and how to optimize the formula and preparation process to obtain the best performance, are also problems that need to be solved. SUMMARY
[0005] The purpose of the present application is to provide a high-toughness anti-cracking waterproof coating containing a self-repairing factor and a preparation method, which has high toughness, excellent anti-cracking performance, and good self-repairing function, thereby prolonging the service life of the waterproof coating and reducing maintenance costs.
[0006] The purpose of the present application can be achieved by the following technical solutions: A high-toughness anti-cracking waterproof coating containing a self-repairing factor, comprising the following components by weight fraction: 40-60 parts of an acrylate-polyurethane blended emulsion; 5-15 parts of HDI microcapsules, the core material of the HDI microcapsules being HDI and nano calcium carbonate, and the wall material being a polyurethane-silicon dioxide hybrid material; 0.5-2 parts of carbon nanotubes; Colorants 20-40 parts; Auxiliaries 0.5-8 parts; and Solvent as needed.
[0007] Preferably, the acrylic ester-polyurethane polymer morphology of the acrylic ester-polyurethane hybrid emulsion is a core-shell assembly morphology or an interpenetrating network / IPN assembly morphology, so as to improve its crack resistance and compatibility.
[0008] Preferably, the mass ratio of the acrylic ester emulsion and the polyurethane emulsion in the acrylic ester-polyurethane hybrid emulsion is 1-3:1, more preferably 2:1.
[0009] Preferably, the preparation method of the acrylic ester-polyurethane hybrid emulsion is: mixing the acrylic ester emulsion and the polyurethane emulsion in proportion, adding an appropriate amount of emulsifier and crosslinking agent, stirring at a speed of 300-500 rpm for 30-60 minutes to obtain the acrylic ester-polyurethane hybrid emulsion.
[0010] Specifically, in the preparation of the acrylic ester-polyurethane hybrid emulsion, the emulsifier is preferably a complex system of anionic and non-ionic emulsifiers, more preferably the emulsifier is a complex formed by sodium dodecyl sulfate (SDS) and polyoxyethylene octylphenol ether (OP-10) in a mass ratio of 1-2:1. The crosslinking agent is at least one of aziridine crosslinking agent, isocyanate crosslinking agent, water-based HDI trimer, epoxy crosslinking agent, polyethylene glycol diglycidyl ether, and metal chelate crosslinking agent.
[0011] Further, the amount of the emulsifier is 0.5-2% of the total mass of the hybrid emulsion, and the amount of the crosslinking agent is 0.3-1% of the total mass of the hybrid emulsion.
[0012] The elastic network structure of the acrylic ester-polyurethane hybrid emulsion can give the coating good crack resistance and elasticity, so that the coating layer can adapt to the expansion and deformation of the base layer, reduce the cracks caused by the deformation of the base layer, and improve the breaking elongation.
[0013] Preferably, the HDI microcapsule is prepared by interfacial polymerization; the mass ratio of the core material and the wall material of the HDI microcapsule is 1:1-2; in the core material of the HDI microcapsule, the mass ratio of HDI and nano calcium carbonate is 1-3:1; and in the wall material, the weight ratio of polyurethane and nano silicon dioxide is 10:1-20:1, more preferably 15:1.
[0014] When the coating is damaged, the core material of the HDI microcapsule is easily broken due to the rigidity of the silicon dioxide, releasing the hexamethylene diisocyanate (HDI) and nano calcium carbonate in the core material to react with the moisture in the surrounding environment to form polyurethane, filling the cracks and restoring the integrity of the coating. This self-repairing function significantly improves the service life and reliability of the coating.
[0015] Further, the preparation method of the HDI microcapsule is as follows: mixing hexamethylene diisocyanate and nano calcium carbonate in a certain proportion, adding an appropriate amount of dispersant, and stirring to form a core material emulsion; mixing polyurethane prepolymer and nano silicon dioxide in a certain proportion, adding an appropriate amount of catalyst and crosslinking agent, and stirring to form a wall material solution; then adding the core material emulsion into the wall material solution, emulsifying at a speed of 500-800 rpm for 1-2 hours, and then heating to 50-70℃ and reacting for 3-5 hours to obtain the HDI microcapsule.
[0016] Specifically, in the preparation method of the HDI microcapsule, the dispersant used is sodium polycarboxylate, sodium naphthalene sulfonate formaldehyde condensate or sodium lignosulfonate. The HDI is hexamethylene diisocyanate, which can react with active groups in the coating to crosslink; the nano calcium carbonate can act as a filler and a reaction material, and cooperates with the HDI to enhance the performance of the repaired coating.
[0017] The HDI microcapsule has a self-repairing function, and can release the core material to react and solidify with the surrounding material when the coating is damaged, so as to realize self-repairing and improve the waterproof effect and durability of the coating.
[0018] Preferably, the carbon nanotubes are surface-modified by APTES or dopamine. In this way, covalent bonds are formed to improve the dispersibility and interfacial bonding strength.
[0019] Alternatively, in another preferred embodiment of the present application, the carbon nanotubes are pre-treated by acidification. The specific treatment method is as follows: adding the carbon nanotubes into a nitric acid solution with a mass concentration of 5-10%, ultrasonic treating at 60-80℃ for 1-3 hours, then filtering and washing to neutral, and drying at 80-100℃ to obtain acidified carbon nanotubes.
[0020] Preferably, the carbon nanotubes are multi-walled carbon nanotubes; the diameter of the carbon nanotubes is 10-20 nm, and the length is 1-10 microns, more preferably 3-5 microns.
[0021] The carbon nanotubes have excellent mechanical properties, and can significantly improve the toughness of the waterproof coating, increase the tensile strength and modulus, and effectively prevent crack propagation.
[0022] Further, the color filler is at least one of calcium carbonate, talc, kaolin, and titanium dioxide.
[0023] More preferably, the color filler is a mixture of calcium carbonate and talc, and the weight ratio is 1-3:1. Preferably, the weight ratio is 2:1.
[0024] Preferably, the auxiliary agent comprises at least one of dispersant, emulsifier, defoaming agent, catalyst, leveling agent, thickening agent, film forming auxiliary agent and pH regulator.
[0025] Preferably, the auxiliary agent comprises 0.5-2 parts of dispersant, 0.3-1 part of defoaming agent, 0.5-2 parts of thickening agent, 1-3 parts of film forming auxiliary agent and 0.2-0.8 parts of pH regulator.
[0026] Further, the dispersant is sodium polycarboxylate; the defoaming agent is silicone defoaming agent; the thickening agent is hydroxyethyl cellulose; the film forming auxiliary agent is dodecanol ester; and the pH regulator is ammonia water.
[0027] Preferably, the solvent is deionized water or organic solvent to adjust the construction viscosity of the coating. Further, the weight fraction of the solvent is 5-15 parts, and the viscosity of the coating at normal temperature (25℃) is 5000-15000 mPa·s.
[0028] The preparation method of the high-toughness anti-cracking waterproof coating with self-repairing factor as described above comprises the following steps: S1, dispersing carbon nanotubes in an acrylate-polyurethane blended emulsion; S2, sequentially adding HDI microcapsules, pigments and fillers and auxiliary agents, and mixing and dispersing; S3, adding a solvent, adjusting the viscosity of the coating to 5000-15000 mPa·s at 25℃, and obtaining the waterproof coating.
[0029] Preferably, in step S1, the rotation speed for dispersing the carbon nanotubes in the acrylate-polyurethane blended emulsion is 1000-1500 rpm, and the time is 15-30 minutes.
[0030] Preferably, in step S2, the rotation speed for mixing and dispersing is 200-500 rpm, the temperature is 40-60℃, and the time is 30-60 minutes.
[0031] The present application has the following advantages: (1) The present application significantly improves the comprehensive performance of the waterproof coating by simultaneously adding acrylate-polyurethane blended emulsion, HDI microcapsules and carbon nanotubes and other materials in the waterproof coating. Among them, the carbon nanotubes as one-dimensional nanomaterials improve the toughness and strength of the material; the acrylate-polyurethane blended emulsion has both the weather resistance of acrylate and the flexibility of polyurethane, improving the breaking elongation of the coating; and the HDI microcapsules endow the coating with self-repairing function, prolonging the service life.
[0032] (2) The waterproof coating of the present application has good weather resistance, water resistance and chemical corrosion resistance, and can maintain stable performance under different environmental conditions. Especially in special scenes such as floor heating room, bridge, underground garage, etc. The traditional waterproof coating is easy to crack due to thermal expansion and contraction in floor heating room with large temperature change; the bridge structure is easy to crack due to long-term bearing of vehicle load and environmental factors; the underground garage is in a humid environment and may be corroded by chemicals. The waterproof coating of the present application has high toughness and high elongation at break, and can adapt to the expansion and deformation of the base layer caused by changes in temperature, humidity, etc.; at the same time, the self-repairing function can repair the fine cracks caused by temperature or vibration changes in time, ensuring that the waterproof effect can effectively cope with the challenges of temperature change, structure vibration and chemical corrosion, etc.
[0033] (3) The formula of the present application is reasonable, the cost of raw materials is similar to that of waterproof coatings on the market, and has good economic benefits and market competitiveness. At the same time, the introduction of self-repairing factor reduces the maintenance cost, further improves the performance-price ratio of the product. DETAILED DESCRIPTION
[0034] In order to further illustrate the technical means and effects adopted by the present application to achieve the predetermined invention purpose, the specific embodiments, structures, features and effects according to the present application are described in detail as follows.
[0035] Example 1 A high-toughness anti-cracking waterproof coating containing self-repairing factor, which comprises the following components by weight fraction: The preparation steps of the acrylate-polyurethane blended emulsion are as follows: Mix the acrylate emulsion and the polyurethane emulsion in proportion, add 0.5 parts by weight of the emulsifier prepared by compounding SDS and OP-10 in a mass ratio of 1.5:1 and 0.3 parts by weight of aziridine crosslinking agent, and stir at a speed of 400 rpm for 45 minutes to obtain the acrylate-polyurethane blended emulsion.
[0036] The preparation steps of the HDI microcapsule are as follows: a. Core material preparation: Mix hexamethylene diisocyanate (HDI) and nano calcium carbonate in proportion, add 0.5 parts by weight of polycarboxylic acid sodium salt as dispersant, and stir at a speed of 1200 rpm for 20 minutes to form a uniform core material emulsion.
[0037] b. Wall material preparation: Mix the polyurethane prepolymer with nano silicon dioxide in proportion, add an appropriate amount of catalyst and crosslinking agent, and stir at a speed of 800 rpm for 20 minutes.
[0038] c. Microcapsule preparation: The core material emulsion was slowly added to the wall material solution, emulsified at a speed of 600 rpm for 1.5 hours, then warmed to 60℃, and reacted for 4 hours to obtain HDI microcapsules.
[0039] The carbon nanotubes are pre-treated by acidification, and the specific steps are as follows: The carbon nanotubes are added to a 8% nitric acid solution, ultrasonically treated at 70℃ for 2 hours, then filtered and washed to neutral, and dried at 90℃ to obtain acidified carbon nanotubes. Specifically, the preparation method of the waterproof coating is as follows: S1, the pretreated carbon nanotubes are added to the acrylate-polyurethane blended emulsion, and dispersed in a high-speed dispersion machine at a speed of 1200 rpm for 20 minutes.
[0040] S2, HDI microcapsules, pigments and fillers, and additives are sequentially added, and continue to be dispersed for 30 minutes.
[0041] S3, water is added to adjust the viscosity, so that the viscosity of the coating reaches to obtain the final waterproof coating.
[0042] Example 2 A high-toughness anti-cracking waterproof coating containing a self-repairing factor, which comprises the following components by weight fraction: The preparation method of the waterproof coating of Example 2 is the same as that of Example 1.
[0043] Example 3 A high-toughness anti-cracking waterproof coating containing a self-repairing factor, which comprises the following components by weight fraction: The preparation method of the waterproof coating of Example 3 is the same as that of Example 1.
[0044] Example 4 A high-toughness anti-cracking waterproof coating containing a self-repairing factor, which comprises the following components by weight fraction: The preparation method is the same as that of Example 1.
[0045] Comparative Example 1 The difference between this comparative example and Example 1 is that in this comparative example, the acrylate-polyurethane blended emulsion is replaced by 50 parts of acrylate emulsion, and the remaining components, preparation steps and parameters are the same.
[0046] Comparative Example 2 The difference between the present comparative example and Example 1 is that the acrylic ester-polyurethane blended emulsion is replaced by polyurethane emulsion 50 parts in the present comparative example, and the remaining components, preparation steps and parameters are consistent.
[0047] Comparative Example 3 The difference between the present comparative example and Example 1 is that the HDI microcapsule addition amount of the present comparative example is 0, and the remaining components, preparation steps and parameters are consistent.
[0048] Comparative Example 4 The difference between the present comparative example and Example 1 is that the carbon nanotube addition amount of the present comparative example is 0, and the remaining components, preparation steps and parameters are consistent.
[0049] The waterproof coating prepared in Examples 1-4 and Comparative Examples 1-4 is coated on the surface of a flat and clean substrate with a thickness of 1.5 mm, and after complete curing, the following performance tests are carried out respectively: (1) Self-repairing efficiency test: The tensile strength of the coating is tested according to GB / T16777-2008 standard, then a 200 μm wide scratch is made on the coating, and the tensile strength recovery rate of the coating after repair is measured after 24 hours under standard conditions.
[0050] (2) Waterproof performance test The waterproof coating is brushed on a previously waxed glass plate with a thickness of 1.5 mm, and after 7 days, it is placed in an oven at 50±2℃ for 24 hours, taken out and placed for 3 hours, and the impermeability experiment is done, with impermeability of 0.3 MPa. No leakage for 30 minutes is qualified.
[0051] (3) Elongation at break test The waterproof coating is brushed on a previously waxed glass plate with a thickness of 1.5 mm, and after 7 days, it is immersed in 1% alkali water for 7 days, and then baked in a 50℃ oven for 24 hours, and dumbbell-shaped tensile test is done to test the elongation at break.
[0052] The test results are shown in Table 1.
[0053] Table 1 From the test results in Table 1, it can be seen that the tensile strength and self-repairing efficiency of Examples 1-4 are better than those of Comparative Examples 1-4, which indicates that the synergistic effect of carbon nanotubes, acrylic ester-polyurethane blended emulsion and HDI microcapsules and other materials significantly improves the performance of the waterproof coating.
[0054] The above merely describes the preferred embodiments of the present application, and is not intended to limit the present application in any form. Although the present application has been disclosed with the preferred embodiments as above, it is not intended to limit the present application. Any person skilled in the art can make some changes or modifications to the above disclosed technical content to obtain equivalent embodiments with equivalent changes, as long as the changes or modifications do not deviate from the technical solution of the present application. Any modification, change, equivalent change and modification of the above embodiments made according to the technical essence of the present application still belong to the scope of the technical solution of the present application.
Claims
1. A high-toughness, crack-resistant and waterproof coating containing a self-repairing factor, characterized in that: The following components are included in parts by weight: 40-60 parts of acrylate-polyurethane blend emulsion; 5-15 parts of HDI microcapsules, wherein the core material of the HDI microcapsules is HDI and nano-calcium carbonate, and the wall material is a polyurethane-silicon dioxide hybrid material; 0.5-2 parts of carbon nanotubes; 20-40 parts of pigments and fillers; 0.5-8 parts of additives; and Appropriate amount of solvent.
2. A high-toughness, crack-resistant, waterproof coating containing a self-repairing factor according to claim 1, characterized in that: The mass ratio of the acrylate emulsion to the polyurethane emulsion in the acrylate-polyurethane blend emulsion is 1-3:
1.
3. The high-toughness, crack-resistant and waterproof coating containing a self-repairing factor according to claim 1, characterized in that: The HDI microcapsules are prepared by interfacial polymerization; the mass ratio of the core material to the wall material of the HDI microcapsules is 1:1-2; the mass ratio of HDI to nano-calcium carbonate in the core material of the HDI microcapsules is 1-3:1; and the weight ratio of polyurethane to nano-silicon dioxide in the wall material is 10:1-20:
1.
4. The high-toughness, crack-resistant and waterproof coating containing a self-repairing factor according to claim 1, characterized in that: The carbon nanotubes have a diameter of 10-20 nm and a length of 1-10 microns.
5. The high-toughness, crack-resistant and waterproof coating containing a self-repairing factor according to claim 1, characterized in that: The pigment and filler is at least one of calcium carbonate, talc, kaolin and titanium dioxide.
6. The high-toughness, crack-resistant and waterproof coating containing a self-repairing factor according to claim 1, characterized in that: The additives include at least one of a dispersant, an emulsifier, a defoamer, a catalyst, a leveling agent, a thickener, a film-forming aid, and a pH regulator; the solvent is deionized water or an organic solvent, the weight portion of the solvent is 5-15 parts, and the viscosity of the coating at 25° C. is 5000-15000 mPa·s.
7. The high-toughness, crack-resistant and waterproof coating containing a self-repairing factor according to claim 6, characterized in that: The auxiliary agent includes 0.5-2 parts of a dispersant, 0.3-1 parts of a defoaming agent, 0.5-2 parts of a thickener, 1-3 parts of a film-forming auxiliary agent and 0.2-0.8 parts of a pH regulator.
8. A method for preparing a high-toughness, crack-resistant, waterproof coating containing a self-repairing factor according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: S1, dispersing carbon nanotubes in acrylate-polyurethane blend emulsion; S2, add HDI microcapsules, pigments and fillers and additives in sequence, mix and disperse; S3. Add solvent and adjust the viscosity of the coating to 5000-15000 mPa·s at 25° C. to obtain a waterproof coating.
9. The preparation method according to claim 8, characterized in that In step S1, the carbon nanotubes are dispersed in the acrylate-polyurethane blend emulsion at a speed of 1000-1500 rpm for 15-30 minutes; in step S2, the mixing and dispersion is performed at a speed of 200-500 rpm, a temperature of 40-60° C., and a time of 30-60 minutes.
10. The preparation method according to claim 8, characterized in that The preparation method of the acrylate-polyurethane blend emulsion is as follows: acrylate emulsion and polyurethane emulsion are mixed in proportion, an appropriate amount of emulsifier and cross-linking agent are added, and the mixture is stirred at a rotation speed of 300-500 rpm for 30-60 minutes to obtain the acrylate-polyurethane blend emulsion; The preparation method of the HDI microcapsules comprises: mixing hexamethylene diisocyanate and nano-calcium carbonate in proportion, adding an appropriate amount of dispersant, and stirring to form a core material emulsion; mixing a polyurethane prepolymer and nano-silicon dioxide in proportion, adding an appropriate amount of catalyst and cross-linking agent, and stirring to form a wall material solution; then adding the core material emulsion to the wall material solution, emulsifying at a speed of 500-800 rpm for 1-2 hours, then heating to 50-70° C. and reacting for 3-5 hours to obtain the HDI microcapsules; The carbon nanotubes are pre-treated with acidification; the specific treatment method is: adding the carbon nanotubes to a nitric acid solution with a mass concentration of 5-10%, ultrasonically treating at 60-80°C for 1-3 hours, then filtering and washing to neutrality, and drying at 80-100°C to obtain acidified carbon nanotubes.
Citation Information
Patent Citations
Method for preparing carbon nano tube reinforced epoxy resin self repairing microcapsule
CN102240533A
Hydroxyl-terminated polybutadiene type waterborne polyurethane / acrylate material and preparation method and application thereof
CN112375182A
Waterproof building coating and preparation method thereof
CN116285532A
Self-repairing insulating material for electrical equipment and preparation method of self-repairing insulating material
CN116574437A
Long-acting super-hydrophobic microcapsule as well as preparation method and application thereof
CN119281239A
